2021
DOI: 10.1039/d1cc00124h
|View full text |Cite
|
Sign up to set email alerts
|

UV-induced photolysis of polyurethanes

Abstract: Waste production associated with the use of non-degradable materials in packaging is a growing cause of environmental concern, with the polyurethane (PU) class being notorious for their lack of degradability....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In addition to the exploration of Norrish-type reactions for photoinitiation, the photorelease of preformed polymer blocks and networks via Norrish pathways was also mapped. In two separate studies, , o -nitrobenzyl moieties were explored as potential photolytic units that could be incorporated into polymers to facilitate on-demand degradation. When the o -nitrobenzyl was modified by substituting two alcohol groups (Figure , R8 ) and an action plot was recorded, it was surprisingly found that the peak reactivity was only red-shifted by 10 nm relative to the absorption maximum (λ max = 350 nm) associated with the NO bond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the exploration of Norrish-type reactions for photoinitiation, the photorelease of preformed polymer blocks and networks via Norrish pathways was also mapped. In two separate studies, , o -nitrobenzyl moieties were explored as potential photolytic units that could be incorporated into polymers to facilitate on-demand degradation. When the o -nitrobenzyl was modified by substituting two alcohol groups (Figure , R8 ) and an action plot was recorded, it was surprisingly found that the peak reactivity was only red-shifted by 10 nm relative to the absorption maximum (λ max = 350 nm) associated with the NO bond.…”
Section: Discussionmentioning
confidence: 99%
“…Molar extinction spectra (solid curves, left axis) and adjusted action plot yields (symbols, right axis) of various photochemical release reactions for photodegradation. For ease of comparison, percentage yields were adapted from the literature ,, and normalized by the number of photoreactive units in solution and the number of photons delivered to the sample to give adjusted % yields. The inset highlights the low-intensity absorption region.…”
Section: Discussionmentioning
confidence: 99%
“…In an exemplary manner, photosensitive o ‐nitrobenzyl moieties were introduced into a polyurethane (in which, the strong urethane linkage and often high degree of crosslinking make them a challenge to degrade without damaging the environment) as structural units. [ 15 ] Those respective light‐responsive units have enabled the polymer to be broken down upon exposure to UV light. Accordingly, this specific approach is postulated to aid the development of polyurethane‐based degradable packaging and adhesives.…”
Section: Green Chemistrymentioning
confidence: 99%
“…In 2011, our group introduced, for the first time, a new class of photodegradable polymers based on poly(ketals/acetals), exhibiting main-chain scission at incredibly low irradiation doses (10 mJ cm −2 ) compared to other polymeric materials [ 7 , 8 ]. More recently, Kowollik and co-workers reported the synthesis of main-chain photodegradable polyurethanes by introducing ONB moieties along the backbone of a polyurethane chain, and studied the degradation profiles of these materials both in solution and on thin films using a nanosecond pulsed laser at 340 nm [ 9 ].…”
Section: Introductionmentioning
confidence: 99%